The Relationship between Cinema and Social Policy: An Examination within the Context of Welfare Regimes - Benli, Abdurrahman; Peri, Dilek (Advances in Social Sciences Research Journal, 2026)
This study aims to examine how post-1980 social policies in different countries have been reflected in the life experiences of individuals through cinematic representations, within the framework of welfare regimes theory. The main subject of the research is to reveal how social policy practices gain meaning in social reality, not only as institutional arrangements but also through cultural narratives. In this regard, the study aims to make visible the everyday life dimension of social policy by relating the welfare regimes literature to cinema and to contribute to the literature by proposing an interdisciplinary analysis. A qualitative research approach has been adopted in the study; selected films from countries representing different welfare regimes have been analyzed from a social policy perspective. Themes of labour, family, state, social assistance, solidarity, and exclusion have been examined through sample film narratives corresponding to post-communist, Southern European, social democratic, conservative-corporatist, and liberal welfare regimes. The study concludes that welfare regimes are not only institutional structures but also social practices that shape the experiences of individuals, and that cinema offers a powerful analytical field that makes these experiences visible. It was also concluded that the success of social policy should be evaluated not only in terms of material security, but also in conjunction with rights, participation, dignity, and social relations.